EXPLORİNG SUBJECT MATTER KNOWLEDGE OF SOME TEACHERS İN THE SENİOR PHASE NATURAL SCİENCE CLASSROOM - Ndivhuwo Prudence Netshivhumbe (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The purpose of this interpretative qualitative study was to examine the subject matter knowledge of senior phase natural science teachers in some of the schools positioned in the Vhembe district of the Limpopo province. A Classroom Practice Diagnostic Framework has been used as a theoretical framework for this study. Classroom observations and interviews were used to collect data from natural science teachers. The results of the study show that teachers have subject matter knowledge as they were able to teach natural science subject to their learners, clarify misconceptions and learners were able to relate what they are taught in natural science with their environment. However, the teachers did not specialised with natural sciences in their teaching qualifications. Furthermore, teachers employed different methods such as questioning, demonstrations, examples and discussions which encouraged and motivated learners to actively participate in their learning. The findings also revealed that teachers used different materials to support their classroom practices and to assist learners in understanding the concepts taught. It is recommended that teachers should be encouraged to attend subject matter knowledge continuous development programmes to enhance their knowledge in all subjects they teach for learners to have a good foundation and interest on their school subjects.